"From Aphrodite to Kuan Yin"—"The Tao of Venus" and its Modern Genealogy: Invoking Ancient Goddesses in Cosm(et)ic Acupuncture. (12th October 2018) - Renger, Almut-Barbara
Abstract : A recent development of the commercialization of New Age religiosity is the combination of ancient Asian traditions with elements of European history—even ancient mythography—and modern psychotherapy, on the assumption, increasingly prevalent since 1800, of a common origin of all religions. The original Asian methods and their religious and philosophical contexts are reinterpreted to make them compatible with the cognitive habits and needs of modern Western recipients, particularly as regards the contemporary ideals of health, beauty and youth.